Prevalence and risk factors of posttraumatic stress symptoms among Internally Displaced Christian couples in Erbil, Iraq - Rofo, Sana; Gelyana, Lina; Moramarco, Stefania; Alhanabadi, Luma H. H.; Basa, Faiq B.; Dellagiulia, Antonio; Emberti Gialloreti, Leonardo (Frontiers in Public Health, 2023)
Background: Research about the impact of war and displacement experiences on the mental health of Internally Displaced People (IDPs) has recently grown. However, a limited number of studies focus on minorities. The objective of the present preliminary study was to estimate the prevalence of symptoms suggestive of post-traumatic stress disorder (PTSD) among IDPs who live outside camps and belong to the Christian minority in Iraq, and to identify possible predictors. Methods: Overall, 108 internally displaced Christians (54 married couples) participated in the study. Traumatic events and post-traumatic stress symptoms (PTSS) were assessed using the Harvard Trauma Questionnaire. Multivariable linear regression models were used to investigate possible predictors of PTS symptoms. Multivariable logistic regression models have been developed to estimate the odds of presenting symptoms suggestive of PTSD. Results: Results demonstrated high rates of trauma exposure, with all participants having experienced at least three traumatic events. The estimated prevalence of symptoms suggestive of PTSD was 20.3%. A low economic status, the number of traumatic events, and a second experience of displacement were associated with an increased PTSD symptomatology. Five traumatic events were identified as the main predictors of symptoms suggestive of PTSD. Conclusion: Findings from the current preliminary study indicated the impact of war-related traumatic events on IDPs’ mental health and the negative effects of post-displacement experiences. These findings may have important implications for setting up psychosocial interventions, as well as for further promoting physical and mental health services among these populations.